2022
DOI: 10.7759/cureus.29459
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 Vaccine Hesitancy Through an Organizational Behaviour Lens

Abstract: Vaccine hesitancy during the COVID-19 pandemic has been a worldwide public health challenge. Organizational behaviour, the study of people’s behaviours in organizational settings, can be used to identify the behavioural drivers contributing to vaccine hesitancy and to develop targeted strategies to combat those drivers and improve vaccine uptake. Some common behaviours driving vaccine hesitancy arise from individualism, motivation, attitude, perception, groupthink, heuristics and cognitive bias. Organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Conversely, in China, where vaccine hesitancy was lower, a more collectivist culture framework prevails [ 29 , 30 ]. Previous research has found that individualistic attitudes can contribute to vaccine hesitancy, whereas collectivist orientations tend to mitigate such hesitancy [ 31 ]. How this paradigm can be applied to each country, is uncertain, given large diversities of cultures within country.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in China, where vaccine hesitancy was lower, a more collectivist culture framework prevails [ 29 , 30 ]. Previous research has found that individualistic attitudes can contribute to vaccine hesitancy, whereas collectivist orientations tend to mitigate such hesitancy [ 31 ]. How this paradigm can be applied to each country, is uncertain, given large diversities of cultures within country.…”
Section: Discussionmentioning
confidence: 99%